Durable response to olaparib plus continued PD-1 blockade in germline PALB2-mutated triple-negative breast cancer with leptomeningeal metastasis - Yulei Wang; Jiali Lin; Yi Zhang; Bo Liang; Xin Lin; Xiangqing Chen; Lijuan Guo; Yifang Zhang; Yuxia Chen; Guochun Zhang (Medicine, 2026)
Rationale: Triple-negative breast cancer (TNBC) with germline PALB2 (gPALB2 ) mutations represents a rare but actionable subset sensitive to poly(ADP-ribose) polymerase (PARP) inhibition. However, clinical evidence supporting PARP inhibition combined with programmed cell death protein 1 (PD-1) blockade after progression on prior immunotherapy remains limited, particularly in central nervous system-involved disease. Patient concerns: A 61-year-old woman initially diagnosed with stage I TNBC developed chest wall recurrence and occipital bone metastasis after a 2-year disease-free interval. The disease subsequently progressed to spinal leptomeningeal metastasis, causing complete bilateral lower-limb paralysis. Diagnoses: Recurrent metastatic TNBC with programmed death-ligand 1 expression and leptomeningeal and multiple osseous metastases was diagnosed. Pharmacogenomic profiling identified a pathogenic gPALB2 p.L484* mutation. Interventions: First-line liposomal doxorubicin achieved 9 months of disease control. Second-line nab-paclitaxel plus tislelizumab, a PD-1 inhibitor, provided a progression-free survival of only 2 months. Third-line carboplatin plus tislelizumab induced rapid neurological improvement, but carboplatin was discontinued after 2 months due to hematologic toxicity. Maintenance tislelizumab monotherapy was continued for an additional 5 months until neurological deterioration and a new femoral metastasis indicated disease progression. Olaparib was subsequently added to continued tislelizumab. Outcomes: Following olaparib initiation, bilateral lower-limb muscle strength improved from Medical Research Council grade 0 to grade 2. Follow-up imaging demonstrated marked regression of the leptomeningeal and osseous lesions. The patient achieved a durable progression-free survival of approximately 40 months with acceptable tolerability. Lessons: Identification of a gPALB2 mutation informed the addition of olaparib to continued tislelizumab, leading to sustained disease control in this patient. Although the relative contributions of each component cannot be determined from a single case, this hypothesis-generating observation suggests that PARP inhibitor–based strategies and continuation of PD-1 blockade beyond progression warrant further investigation in carefully selected patients with gPALB2 -mutated TNBC with central nervous system involvement.